2011
DOI: 10.1038/nature10110
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of autistic brain reveals convergent molecular pathology

Abstract: Autism spectrum disorder (ASD) is a common, highly heritable neuro-developmental condition characterized by marked genetic heterogeneity1–3. Thus, a fundamental question is whether autism represents an etiologically heterogeneous disorder in which the myriad genetic or environmental risk factors perturb common underlying molecular pathways in the brain4. Here, we demonstrate consistent differences in transcriptome organization between autistic and normal brain by gene co-expression network analysis. Remarkably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

143
1,843
13
16

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,702 publications
(2,015 citation statements)
references
References 37 publications
143
1,843
13
16
Order By: Relevance
“…Genes involved in synaptic function have been repeatedly shown to play a role in neurological disorders [62,63,65,66]. Recent studies of ASD have identified overrepresentation of CNS development genes in addition to several other pathways [21,65,67]. In our own recent analysis of 209 exomes from patients with sporadic autism, we found that 39% of the de novo disruptive mutations formed a highly interconnected protein-protein interaction network involving beta-catenin upstream and downstream regulation (Figure 3) [52].…”
Section: A Genetic Model Of Neurodevelopmental Diseasementioning
confidence: 76%
“…Genes involved in synaptic function have been repeatedly shown to play a role in neurological disorders [62,63,65,66]. Recent studies of ASD have identified overrepresentation of CNS development genes in addition to several other pathways [21,65,67]. In our own recent analysis of 209 exomes from patients with sporadic autism, we found that 39% of the de novo disruptive mutations formed a highly interconnected protein-protein interaction network involving beta-catenin upstream and downstream regulation (Figure 3) [52].…”
Section: A Genetic Model Of Neurodevelopmental Diseasementioning
confidence: 76%
“…More recent papers studied several brain regions across development. For example, Kang et al (2011) created a network using data from six brain structures across pre-and post-natal development and found modules related to different spatiotemporal profiles 4 , while Voineagu et al (2011) studied changes in expression modules in the autistic brain 7 . In our initial assessment of the first two brains in the Allen Human Brain Atlas 3 , we identified groups of genes related both to major cell types (i.e., astrocytes, choroid plexus, etc.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of studies have suggested the involvement of genetic factors influencing immune function in the etiology of ASD (Gregg et al, 2008;Voineagu et al, 2011). It is possible that such genetic involvement may act as a confounder (the genetic factor increases risk of both infection and ASD, resulting in a spurious association between infection and ASD) or as an instrument (the genetic factor increases risk of infection which then increases risk of ASD) or as an effect modifier (the genetic factor amplifies the deleterious effect of infection on risk of ASD) -but the latter two does not change the result that maternal infection is associated with ASD.…”
Section: Discussionmentioning
confidence: 99%